Towards an IEEE 802.22 (WRAN) based wireless broadband for rural Bangladesh- point-to-point link, coverage, and CPE antenna design - Noor, Omar Faruk; Haider, Arifa; Dipto, Foysal Alam (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2016.